2010
DOI: 10.2109/jcersj2.118.1207
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of MgFe2O4 microsphere using spray dryer for embolization therapy application

Abstract: MgFe 2 O 4 microspheres having a 2032 µm diameter range were prepared by a spray dryer using bead-milled nano-sized particles. A commercial powder having a several µm particle size was bead-milled to an approximate 6.2 nm crystallite size. The microspheres were obtained using the spray dryer when the air pressure was low (0.03 MPa). The yield of the MgFe 2 O 4 2032 µm microspheres was improved by combination of a low air pressure and high ferrite concentration in the slurry. The heat generation ability in an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It has excellent chemical stability with inverse spinel structured, which have found a number of modern technological applications in microwave devices, catalysis, adsorption, gas and humidity sensor, ferrofluid technology, fuel cells, magnetic core of coils and also used in an inorganic pigment [11][12][13]. Aono et al [14] found that MgFe 2 O 4 has the highest heating ability compare to other commercial ferrite powders of MFe 2 O 4 (M = Mg, Mn, Fe, Co, Ni, Cu and Sr) in alternating magnetic field which is one of the interesting applications in hyperthermia therapy. In addition, these MgFe 2 O 4 nanoparticles would be suitable for the use in the human body, because the elements present in these material are nontoxic [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has excellent chemical stability with inverse spinel structured, which have found a number of modern technological applications in microwave devices, catalysis, adsorption, gas and humidity sensor, ferrofluid technology, fuel cells, magnetic core of coils and also used in an inorganic pigment [11][12][13]. Aono et al [14] found that MgFe 2 O 4 has the highest heating ability compare to other commercial ferrite powders of MFe 2 O 4 (M = Mg, Mn, Fe, Co, Ni, Cu and Sr) in alternating magnetic field which is one of the interesting applications in hyperthermia therapy. In addition, these MgFe 2 O 4 nanoparticles would be suitable for the use in the human body, because the elements present in these material are nontoxic [15].…”
Section: Introductionmentioning
confidence: 99%
“…51),52) Bead-milled MgFe 2 O 4 and Y 3 Fe 5 O 12 were tested for the preparation of microspheres using the spray-drying method. 53),54) Figure 11 shows a spray-drier used for the preparation of the microspheres. The slurry for the spray-drier was obtained as a mixture of the bead-milled Y 3 Fe 5 O 12 and purified water, and then sprayed by heated air at 200°C as small droplets by the spraydrier with an nozzle atomizer.…”
Section: Preparation Of Microspheres For Embolization Methodsmentioning
confidence: 99%
“…The microspheres with a 20-30 μm diameter range could be obtained by spray drying using a water-based slurry of ferrite MgFe 2 O 4 nanopowders [21].…”
Section: Introductionmentioning
confidence: 99%